Financial Performance Evaluation of The Islamic Banks as compared with the Conventional banks Operating in Jordan in Light of Global Financial Crisis - Basoul, Medhat Majed; Abdel Ghani, Yousef Hani (Journal of Economic, Administrative and Legal Sciences, 2018)
The purpose of this study was to the statement of the impact of the global financial crisis on Islamic banks operating in Jordan compared to their impact on traditional banks, and the study used a set of indicators to assess the economic performance of the study sample banks before the global financial crisis and during.The study concluded that the economic performance of Islamic banks is better than conventional banks before the crisis in some of the indicators, while conventional banks perform better in other indicators, but in light of the financial crisis, the economic performance of Islamic banks was better than conventional banks set of ratios, including: the proportion of workers in the bank to the total of the Worlds in the banking sector, and the credit facilities provided for the construction sector and trade sector, the public and thus on employment, the proportion of deposits the bank to total deposits, which improve the performance of Islamic banks in the global financial crisis compared with before the global financial crisis.
Keywords: Islamic banks; conventional banks; global financial crisis